Motor Dynamics Underlying Cargo Transport by Pairs of Kinesin-1 and Kinesin-3 Motors - Arpağ, Göker (Biophys J, 2019)
Intracellular cargo transport by kinesin family motor proteins is crucial for many cellular processes, particularly vesicle transport in axons and dendrites. In a number of cases, the transport of specific cargo is carried out by two classes of kinesins that move at different speeds and thus compete during transport. Despite advances in single-molecule characterization and modeling approaches, many questions remain regarding the effect of intermotor tension on motor attachment/reattachment rates during cooperative multimotor transport. To understand the motor dynamics underlying multimotor transport, we analyzed the complexes of kinesin-1 and kinesin-3 motors attached through protein scaffolds moving on immobilized microtubules in vitro. To interpret the observed behavior, simulations were carried out using a model that incorporated motor stepping, attachment/detachment rates, and intermotor force generation. In single-molecule experiments, isolated kinesin-3 motors moved twofold faster and had threefold higher landing rates than kinesin-1. When the positively charged loop 12 of kinesin-3 was swapped with that of kinesin-1, the landing rates reversed, indicating that this “K-loop” is a key determinant of the motor reattachment rate. In contrast, swapping loop 12 had negligible effects on motor velocities. Two-motor complexes containing one kinesin-1 and one kinesin-3 moved at different speeds depending on the identity of their loop 12, indicating the importance of the motor reattachment rate on the cotransport speed. Simulations of these loop-swapped motors using experimentally derived motor parameters were able to reproduce the experimental results and identify best fit parameters for the motor reattachment rates for this geometry. Simulation results also supported previous work, suggesting that kinesin-3 microtubule detachment is very sensitive to load. Overall, the simulations demonstrate that the transport behavior of cargo carried by pairs of kinesin-1 and -3 motors are determined by three properties that differ between these two families: the unloaded velocity, the load dependence of detachment, and the motor reattachment rate.